Proceedings of the ACM SIGGRAPH/Eurographics Symposium on Non-Photorealistic Animation and Rendering 2011
DOI: 10.1145/2024676.2024678
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of emotional response to non-photorealistic images

Abstract: Non-photorealistic rendering (NPR) algorithms are used to produce stylized images, and have been evaluated on the aesthetic qualities of the resulting images. NPR-produced images have been used for aesthetic and practical reasons in media intended to produce an emotional reaction in a consumer (e.g., computer games, films, advertisements, and websites); however, it is not understood how the use of these algorithms affects the emotion portrayed in an image. We conducted a study of subjective emotional response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…They found that some techniques preserve the emotions better than others, but that the effect might be attributed to the amount of detail that was preserved by a given technique. It is interesting that this muting of emotion to some degree stands in contrast to the observations of Duke et al [10] and Halper et al [21,22], but this effect can probably be explained based on the different types of stylization employed by both evaluations: Mandryk et al [41] and Mould et al [44] examined image-based (i.e., mostly spacefilling) techniques in which the style's amplitude (as measured in tone or color) is reduced by the NPR technique from the original photograph due to the introduced abstraction, while Duke et al and Halper et al's analysis of emotion (social perception and judgment) was based on line drawings in which the strong emotion (fear) was caused by a high-amplitude zig-zaggy style.…”
Section: Providing a General Motivation For Nprmentioning
confidence: 70%
See 2 more Smart Citations
“…They found that some techniques preserve the emotions better than others, but that the effect might be attributed to the amount of detail that was preserved by a given technique. It is interesting that this muting of emotion to some degree stands in contrast to the observations of Duke et al [10] and Halper et al [21,22], but this effect can probably be explained based on the different types of stylization employed by both evaluations: Mandryk et al [41] and Mould et al [44] examined image-based (i.e., mostly spacefilling) techniques in which the style's amplitude (as measured in tone or color) is reduced by the NPR technique from the original photograph due to the introduced abstraction, while Duke et al and Halper et al's analysis of emotion (social perception and judgment) was based on line drawings in which the strong emotion (fear) was caused by a high-amplitude zig-zaggy style.…”
Section: Providing a General Motivation For Nprmentioning
confidence: 70%
“…The first aspect, the effect that NPR imagery has on people's emotions, has recently been studied in detail by Mandryk et al [41] and Mould et al [44] who looked at how the stylization of photographs changed people's emotional response to the images. They selected 18 images covering a wide range of topics from the IAPS image database (created specifically as affective stimuli and with known emotional content), and examined the emotional response of 42 participants.…”
Section: Providing a General Motivation For Nprmentioning
confidence: 99%
See 1 more Smart Citation
“…Mandryk et al [2011] resp. , for instance, studied people's emotional response to stylized images and found that emotional responses was generally muted, and that responses concentrated around neutral feelings.…”
Section: Introductionmentioning
confidence: 95%
“…In contrast, non-photorealistic image is important for conveying the information and adding the simplicity of complex objects. NPR images distinguished over photographs in many practical advantages such as lack of dispersion (e.g., in scientific illustration), focusing and clarification of essential details (e.g., in maps, caricature and technical illustrations) (Liew Suet Fun et al, 2004;Mandryk et al, 2011).…”
Section: Introductionmentioning
confidence: 99%